A long decade of gendering social policy in Latin America: transformative steps and inequality traps - Martínez Franzoni, Juliana (2018)
Did recent social policy expansion entail positive changes for women and for gender equality in Latin America? This chapter argues that, overall, this expansion brought good news for women’s visibility as subjects of policy but a more mixed record in whether state programmes reinforced or contributed to alter gender inequality in the region. On the one hand, policy developments increased the proportion of women with their own incomes, improved women’s access to old-age benefits in their own right and timidly moved towards a reorganization of care beyond families and unpaid female, motherly work. Together with larger labour market participation, these developments have had a positive transformative effect on women’s lives. On the other hand, the scope and quality of benefits that matter for women and for gender equality are often limited, and social policy still leaves much to markets, families and the male-breadwinner model. This in some cases reinforces women’s role as mothers and exclusive caregivers, and in general limits the transformative potential of policy developments to close gender and social gaps. Altogether, the gendering of social policy creates a whole new agenda to confront and redress these persistent gender and social inequality traps.